Gonad maturity and gonadal somatic index of blue swimming crab Portunus pelagicus harvested from Spermonde Archipelago, South Sulawesi, Indonesia - Muh. Saleh Nurdin; Fauziah Azmi; Teuku Fadlon Haser (Aceh Journal of Animal Science, 2021)
Reproductive biology is one of the biological aspects that needed to formulate responsible management of blue swimming crab (BSC). The crab is one of the commercial fisheries commodities in South Sulawesi, Indonesia. Presently no information on the reproductive biology of this crab from Spermonde Archipelago, Sout Sulawesi. Therefore, the study aimed to analyze and compare gonad maturity stage(GMS)andgonadalsomaticindex(GSI)oftheBSCcaughtonthreeecosystemsnamelycoralreef,seagrass,andmangrovein Salemo Island, Spermonde Archipelago. GMS and GSI were analyzed descriptively for five months from March to July 2015. Results indicate there was a difference in GMS of the BSC caught in mangroves, seagrass, and coral reef. Generally, mangrove was dominated by immature BSC with GMS I and GMS II, while the BSC caught in the seagrass and coral reef BSC were dominantly mature and spawn GMS III, IV, and V. GSI BSC caught in mangrove ecosystem are smaller than GSI BSC caught in seagrass and coral reef ecosystems. Seagrass and coral reef ecosystems suitable for development no-take zone of the BSC.